25% oral dextrose as analgesia during neonatal immunisation with BCG - Mundol, Tania Habib; Prabhu, Anitha S.; Saldanha, Prakash R. M. (International Journal of Contemporary Pediatrics, 2018)
Background: Various animal studies have shown that repeated painful exposures can have deleterious long-term effects on neonates. Sick newborns are exposed to multiple painful procedures such as venipunctures, suctioning even removal of plasters. There are various physiologic and behavioral indicators of pain used in various standardized pain scales such as NIPS, NFCS, FLACC scale and Wong-Baker Faces pain scale. Sucrose, as an analgesic, has been used and recommended for minor painful procedures in neonates. The optimal dose of oral sucrose has not been established. The objective of this study was to study the analgesic effect of oral administration of 2 ml of 25% oral dextrose during neonatal immunization with BCG vaccine using NIPS (Neonatal/Infant Pain Scale). Methods: 40 consecutively selected newborns were given 2 ml of 25% oral dextrose solution 2 minutes prior to receiving the routine intradermal BCG vaccination. 40 consecutively selected newborns served as controls. The pain response in both groups was assessed using the standardized Neonatal Infant Pain Scale (NIPS). Results: Of the total 80 neonates included in the study, 40 were included in the dextrose group and 40 served as controls. 77.5% of the dextrose group were term babies compared to 72.5% in the control group. 20% of the dextrose group showed a NIPS score ≥6 while 40% in the control group had a similar NIPS score. Conclusions: A total of 80 newborns were included in this study, of which 40 (22 males, 18 females) received 25% oral dextrose solution prior to the BCG vaccine. The group which received dextrose was found to have less indicators of pain such as change in breathing pattern, cry and facial expression.